1987
DOI: 10.1111/j.1745-6592.1987.tb01044.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Selected Sampling Equipment and Procedures on the Concentrations of Trichloroethylene and Related Compounds in Ground Water Samples

Abstract: Variations in concentrations of trichloroethylene and related compounds in ground water obtained from seven ground water samplers were used to compare the performance of three submersible pumps, a centrifugal pump, two peristaltic pumps, and a bailer. Two‐ and 4‐inch diameter submersible pumps and a centrifugal pump produced samples whose trichloroethylene concentrations, on the average, did not differ significantly from each other. Ground water samples collected by using a peristaltic pump and silicone tubing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 4 publications
1
12
0
Order By: Relevance
“…These pumps have an advantage over centrifugal pumps (see below) in that the sample only comes into contact with the tubing. However, silicone tubing is most commonly used, to provide the required flexibility, and this is not suitable for sampling organics due to its propensity to absorb organic compounds (Barcelona et al, 1985;Pearsall and Eckhardt (1987). The loss of volatiles using peristaltic pumps has been investigated by a number of workers; Barker and Dickhout (1988) found concentrations of volatile halocarbons 23 to 33 percent lower than other pumps tested and concluded that degassing was a problem with this pump.…”
Section: Peristaltic Pumpsmentioning
confidence: 99%
“…These pumps have an advantage over centrifugal pumps (see below) in that the sample only comes into contact with the tubing. However, silicone tubing is most commonly used, to provide the required flexibility, and this is not suitable for sampling organics due to its propensity to absorb organic compounds (Barcelona et al, 1985;Pearsall and Eckhardt (1987). The loss of volatiles using peristaltic pumps has been investigated by a number of workers; Barker and Dickhout (1988) found concentrations of volatile halocarbons 23 to 33 percent lower than other pumps tested and concluded that degassing was a problem with this pump.…”
Section: Peristaltic Pumpsmentioning
confidence: 99%
“…The six pumps considered perform purging and sampling functions without significant loss of volatile constituents from the water samples. This statement is supported by numerous reports of relevant research in the scientific literature Ho 1983;Unwin 1984;Barcelona et al 1984Stolzenburg and Nichols 1985;Garske and Schock 1986;Muska et al 1986;Pearsall and Eckhardt 1987;Imbrigiotta et al 1988;Panko and Barth 1988;Pohlmann and Hess 1988;Schalla et al 1988b; Unwin and Maltby 1988;Gibs and Imbrigiotta 1990;Gass et al 1991;Gibs et al 1993;Knobel and Mann 1993;Parker et al 1993).…”
Section: 2mentioning
confidence: 50%
“…During subsequent sampling visits to the well a code number is entered and the control system automatically makes the pump remove water at the desired discharge rate plus or minus less than 10%. While research performed by Yeskis et al (1988) indicates that even conventional submersibles perform similarly to bladder pumps when collecting samples for volatile organic compound analysis, bladder pumps have been generally considered the type of sampling pump that perturbs groundwater samples the least, and studies tend to use it as a reference standard (Barcelona et al 1984;Unwin 1984;Nielsen and Yeates 1985;Muska et al 1986;Boateng 1987a, 1987b;Pearsall and Eckhardt 1987;Imbrigiotta et al 1988;Schalla et al 1988b;Yeskis et al 1988;Gass et al 1991;Paul and Puls 1992;Parker et al 1993;Knobal and Mann 1993;Puls and Paul 1995).…”
Section: Effect On Sample Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Pump placement, flow rate, and pumping duration were duplicated when wells were resampled. Tests of this sampling procedure have indicated that it provides representative samples of ground water at VOC concentrations between 1 and 1,000 /Jg/L (Pearsall and Eckhardt, 1987). The pump was flushed after each sampling with 2 to 5 gal of clean tap water.…”
Section: We LI Network and Sampling Proceduresmentioning
confidence: 99%